Embedded battle royal [embedded operating systems]. - Santo, S.
In this paper, the author describes how Windows and Linux are extending their competition for the desktop to cell phones and set-top boxes in the form of embedded microprocessor systems. In addition, he questions whether traditional embedded operating systems are up to the challenge
Keywords: Linux; Windows; Cell phones; Embedded operating systems; Microprocessor systems; Set-top boxes